2017
DOI: 10.3354/meps12163
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an established marine protected area at sustaining a queen conch Lobatus gigas population during three decades of monitoring

Abstract: Marine Protected Areas (MPAs) are designed to conserve and preserve the ecosystems and cultural resources of the ocean. In theory, protected populations flourish, replenish adjacent regions, and are self-sustaining. However, describing the efficacy of MPAs requires long-term monitoring. Queen conch Lobatus gigas are iconic Caribbean denizens with populations that have been decimated by overfishing and are slow to rebound due to density-dependent breeding. The Exuma Cays Land and Sea Park (ECLSP) is a well-enfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 51 publications
(52 reference statements)
5
35
0
Order By: Relevance
“…Given the heavy reliance on RZs to the overall management of conch in Belize and elsewhere, it is critical to quantify the net spillover to the surrounding fishing grounds (Acosta, ; Hernandez‐Lamb et al, ; Singh‐Renton et al, ; Tewfik & Béné, ). Such a strategy should also strive for a RZ network that includes the entire life cycle (Kough et al, ) and associated components of the fishery for conch (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the heavy reliance on RZs to the overall management of conch in Belize and elsewhere, it is critical to quantify the net spillover to the surrounding fishing grounds (Acosta, ; Hernandez‐Lamb et al, ; Singh‐Renton et al, ; Tewfik & Béné, ). Such a strategy should also strive for a RZ network that includes the entire life cycle (Kough et al, ) and associated components of the fishery for conch (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as conchs age, the volume within the shell, regardless of maximum SL attained, decreases (Randall, ), resulting in old conchs (lip thickness, LT > 22 mm) having slight decreases in overall soft tissue mass and gonad mass, indicating some decrease in fecundity but no loss in reproductive capability when compared with younger adult conchs of similar SL (Stoner, Mueller, et al, c). This indicates that overall fecundity is mostly a function of size (maximum SL achieved as juveniles) at onset of lip formation, but also age (relative shell volume), and suggests that thick‐lipped small SL phenotype (‘samba’) queen conchs have smaller tissue and gonads and therefore lower fecundity (Kough, Cronin, Skubel, Belak, & Stoner, ; Stoner, Mueller, et al, ). In very old conchs of any size the rate of external bio‐erosion of the shell, varying depending on the local environment, may outpace the growth of the interior areas of the shell, resulting in a reduced SL while making LT an unsatisfactory means of absolute ageing when compared with younger adults (Buckland, ; Stoner & Sandt, ; Tewfik, ; Tewfik, Guzmán, & Hácome, ).…”
Section: Introductionmentioning
confidence: 99%
“…No‐take marine protected areas (MPAs) have also been a partially effective management strategy for queen conch. The Exuma Cays Land and Sea Park (ECLSP) had historically healthy adult queen conch populations, but repeated surveys have shown that deep‐water populations inside the no‐take MPA are sharply declining and the overall population is ageing with little signs of recruitment (Kough, Cronin, Skubel, Belak, & Stoner, ). However, conch densities inside the ECLSP still surpass those outside the MPA (Stoner et al., ).…”
Section: Species At Riskmentioning
confidence: 99%
“…Clines in species’ phenotypic traits are an important part of ecological and evolutionary studies (Levin, ) and can be extremely useful in quantifying the degree of connectivity among populations and for delineating population boundaries (Jones, Srinivasan, & Almany, ; Kough, Cronin, Skubel, Belak, & Stoner, ; Leis, van Herwerden, & Patterson, ; Woods & Jonasson, ). Geographical patterns in morphology can result from direct environmental control of physiological processes and body shape (Vermeij, ), differential adaptation to variable surroundings (Pinkert, Brandl, & Zeuss, ; Reinecke et al., ), or, alternatively, from random changes in genetically distinct populations (Kimura & Maruyama, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a noticeable paucity of knowledge on geographical patterns, population connectivity, and within‐species diversity in marine species (Conover, Clarke, Munch, & Wagner, ), particularly in deep sea (>200 m depth) habitats (Mengerink et al., ; Taylor & Roterman, ) but also in shallower, coastal seas. These coastal zones are home to many commercially harvested gastropods, for which spatial management and conservation strategies are hampered by a scarcity of data on population processes (Jones et al., ; Kough et al., ; Leis et al., ; Machkour‐M'Rabet, Cruz‐Medina, García‐De León, De Jesús‐Navarrete, & Hénaut, ; Woods & Jonasson, ). Moreover, marine molluscs with direct development (e.g.…”
Section: Introductionmentioning
confidence: 99%